2022
DOI: 10.1109/taffc.2020.3029440
|View full text |Cite
|
Sign up to set email alerts
|

Doing and Feeling: Relationships Between Moods, Productivity and Task-Switching

Abstract: Digital technology influences behaviours, moods and wellbeing. The relationships are complex, but users are increasingly interested in finding how to balance a digital life with psychological wellbeing. We describe MindGauge, a mobile app that helps users collect and analyse data about moods and behaviours. In this study, we collected computer and smartphone usage and self-reports from 72 participants by using MindGauge and RescueTime. We examined the relationship between productivity, task-switching, mood and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…In recent years, researchers have found a strong connection between frequent task switching and negative emotions 9 . For example, in the process of software development, task-switching distracts the developers and shifts the developers' attention, requiring additional immersion time to focus 10 .…”
Section: Backgroundsmentioning
confidence: 99%
“…In recent years, researchers have found a strong connection between frequent task switching and negative emotions 9 . For example, in the process of software development, task-switching distracts the developers and shifts the developers' attention, requiring additional immersion time to focus 10 .…”
Section: Backgroundsmentioning
confidence: 99%
“…Studies with interventions such as diary writing, focus groups, interviews, and questionnaire were mainly theoretical and had the goal of understanding relationships between multiple variables within HCI and different technologies. For example, the authors in [121] studied the mobile usage and its impact on users' emotions, similarly, [116] explored the relationships between users' moods and life-style with task switching online and productivity using Mindgauge and RescueTime which are free mobile applications available online. The authors in [70] studied social networking site (SNS) features and their impact on procrastination habits, and the team in [72] studied the relationship between personal and cultural traits on the acceptance and rejection of joining online peer support groups for combating digital addiction.…”
Section: Other Interventionsmentioning
confidence: 99%
“…The results showed that the correlation between switching ability and subsequent operation time was only found when there was a high workload in both tasks. In recent years, researchers have also found a strong connection between frequent task switching and negative emotions 11 . For example, Shan et al explored the rationale for the effects on mental workload and performance after task interruptions.…”
Section: Backgroundsmentioning
confidence: 99%